Вперед, на Запад! Операция "Багратион" - Дайнес Владимир Оттович (1941-1945. Великая и неизвестная война, 2020)
Экземпляры: РБ (20210406☮) / Инвентарный номер: 61518 / Цена: 200.00 / Авт.знак: Д 14 / ГРНТИ: 03.23.55 / ББК: 63.3(2)622